Potensi Karbon Aktif dari Kulit Durian dengan Aktivator HCl untuk Immobilisasi Asam Lemak Hidroksamat - Muhsinun, Muhsinun; Hidayat, Syamsul (Varied Knowledge Journal, 2025)
Durian peel waste has the potential to be converted into high-value activated carbon through carbonization and chemical activation processes. This study aims to investigate the potential of durian peel–derived activated carbon, activated using HCl, as a material for immobilizing hydroxamic fatty acids. The research process included raw material preparation, carbonization at 500–600 °C, chemical activation with varying HCl concentrations (0.5 M, 1 M, 2 M), and characterization using Fourier Transform Infrared (FTIR), Brunauer–Emmett–Teller (BET), and Scanning Electron Microscopy (SEM). The immobilization capacity test was conducted by measuring the amount of hydroxamic fatty acid bound to the activated carbon surface. Results showed that HCl activation reduced the activated carbon yield to 28–31%, but significantly improved its quality. FTIR analysis revealed the appearance of hydroxyl and carbonyl groups, while BET analysis demonstrated an increase in surface area from 350 m²/g (non-activated) to 910 m²/g at a concentration of 2 M. SEM observations confirmed the formation of a more regular pore structure, although excessively high concentrations caused surface cracking. Adsorption tests indicated that immobilization capacity increased from 25 mg/g (non-activated) to 80 mg/g at 2 M activation, with optimum conditions achieved at 1 M, providing a balance between surface area, structural stability, and adsorption capacity. This study highlights the potential of durian peel–based activated carbon as a support material for bioactive immobilization, with promising applications in catalysis, pharmaceuticals, and environmentally friendly bioprocesses.